Joshua Bowen Smith correspondence - Smith, Joshua Bowen, 1813-1879.
Letters, invitations to social functions, notices of meetings, and notification of Smith's selection as an alternate delegate to the 1876 Republican National Convention.
Caterer, abolitionist, and state legislator of Boston, Mass.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Massachusetts -- Politics and government; Abolitionists; Caterers; Legislators -- Massachusetts